Visual Analysis of The ḤQM Model And Prospects for Authentic Innovation In Islamic Finance - Abderrazak Belabes (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2025)
The aim of this study is to show, through the conceptual system ḤQM (Ḥ: ḥukm, Q: qāʿidah, M: maqṣad), the need to deepen our understanding of authentic innovation in Islamic finance. This study argues that prevailing debates on Islamic financial products are dominated by dichotomous notions grounded in linear modes of thinking, which constrain substantive discussion and hinder the development of credible and sustainable solutions. The main findings reveal that when the teleological discourse on the purposes of Sharīʿah is itself framed within linear reasoning, it cannot legitimately be regarded as the highest intellectual achievement of Islamic civilization. Furthermore, incorporating the dimension Q (qāʿidah) enables the dismantling of rigid categorization and hierarchization that characterizes much of the literature polarized between Ḥ and M. By emphasizing the two-dimensional nature of graphs, distinct from the linearity of written discourse, the graphical visualization of the ḤQM conceptual model opens new analytical possibilities, particularly in the domain of data visualization and non-linear reasoning. In addition, the science of jurisprudential maxims allows the formulation of general rules whose epistemological significance lies in the dynamic interaction between parts and wholes. The dominance of linear approaches in the financial industry has produced adverse outcomes, including mimetic and constrained innovation, excessive reliance on standardized products, and the suppression of proactive and systemic innovation. Accordingly, this study concludes that genuinely innovative Islamic finance requires a non-linear approach that integrates interaction, shared risk, and real asset backing, while coherently aligning injunctions, maxims, and the higher objectives of Sharīʿah.